The Potential Role of the Microbiome in the Pathogenesis of Nasal Tumors: A Comprehensive Review - Antonella Loperfido; Davide Rizzo; Bruno Fionda; Luca Mureddu; Andrea Tondo; Luca Tagliaferri; Gianluca Bellocchi; Giovanni Delogu; Francesco Bussu (Medicina)
Cancers of the nose, and especially the nose vestibule, represent a significant challenge for clinicians due to their rarity, the intricate nature of surrounding vital structures, the nonspecific early symptoms, and the etiological factors that are not completely understood. Emerging research suggests that alterations in the nasal microbiome, also known as microbial dysbiosis, may contribute to the pathogenesis of those malignancies through mechanisms involving chronic inflammation, immune modulation, and cellular changes. The aims of this paper are to review the current literature covering the nasal microbiome’s role in carcinogenesis, particularly in the context of squamous cell carcinoma, and to explore how microbial dysbiosis might foster a pro-tumorigenic environment. It further discusses potential future directions for research and therapeutic approaches.